Distribution pattern analysis of passing and receiving locations during the 2022 FIFA World Cup using the measure of spatial entropy - Xiong, X.; Deng, K.; Wu, J.; Cui, Y. (International Journal of Performance Analysis in Sport, 2025)
The study aimed to investigate the spatial distribution patterns of passing and receiving locations during the 2022 FIFA World Cup in different match stages, playing positions and team possession types. Eighteen types of spatial entropy were proposed to evaluate the heterogeneity of passing and receiving locations in 64 matches. T-tests of these entropies were made between teams at the group and knockout stages, and between distinct playing positions. The K-means clustering of each team`s ball-possession per match was employed to divide all matches into two categories, and their differences in entropies were then analysed using one-way ANOVA. Results showed that the teams at the group and knockout stages had significant differences only in goalkeeper entropy (ES = 0.368). The spatial entropy of the goalkeeper exhibited significant differences in comparison to the other positions (ES: -6.71 ~ -4.69). Low ball-possession teams were significantly lower in 8 types of spatial entropies (ES: -1.02 ~ -0.41) compared to their high ball-possession counterparts. Furthermore, only two types of spatial entropies (ES: -0.58 ~ -0.54) differed significantly in the comparison between high and low ball-possession teams. These findings may provide coaches with guidance for implementing targeted defensive strategies and enhancing the team`s passing performance.